PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA CV. TIMMI BERSAUDARA PALEMBANG - Akilah, Akilah (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
The purpose of this study was to determine the effect of work environment and organizational culture together on employee job satisfaction at CV. Timmi Brothers. The population in this study were all employees in the CV. The Timmi Brothers numbered 70 people and also served as a research sample. Methods of data collection using questionnaires and documentation. The analysis technique used in this study is multiple linear regression with the help of SPSS 22.0 software for windows.The results showed that: 1) Together there was a positive and significant influence of work environment and organizational culture on employee job satisfaction on CV. Timmi Brothers. 2) Partially there is a positive and significant influence of the work environment on employee job satisfaction on the CV. Timmi Brothers. 3) Partially there is a positive and significant influence of organizational culture on employee job satisfaction on the CV. Timmi Brothers.